Chloride intracellular channel 1 is overexpression in hepatic tumor and correlates with a poor prognosis. Issue 11 (18th April 2013) - Zhang, Sheng; Wang, Xiao‐Min; Yin, Zhen‐Yu; Zhao, Wen‐Xiu; Zhou, Jian‐Yin; Zhao, Bi‐Xin; Liu, Ping‐Guo
Abstract : Chloride intracellular channel 1 (CLIC1) is expressed in many human tissues and has been reported to be involved in the regulation of cell cycle, cell proliferation, and differentiation. Its roles in human hepatic tumor, however, remain unclear. The aim of this study was to investigate the clinicopathological significance and expression pattern of CLIC1 in human primary hepatic tumors. We examined the expression pattern of CLIC1 mRNA and protein in hepatic tumors using real‐time quantitative RT‐PCR and Western blot, respectively. CLIC1 protein and mRNA levels were significantly higher in cancerous tissues compared with corresponding normal tissue. In 85 hepatic tumor tissues, CLIC1 was significantly higher in 69 cases (81.2%), as determined by immunohistochemical staining. Increased CLIC1 expression was correlated with tumor size (p = 0.021), distant metastasis (p = 0.025), pathological TNM (pTNM) stage (p = 0.023), and poor survival (25.11 ± 2.27 vs 45.29 ± 4.28 months, p = 0.001). Our data show that increased CLIC1 protein expression is associated with clinicopathological factors and a poor prognosis of hepatic tumors, and suggest that CLIC1 might represent a valuable prognostic marker for human hepatic tumors.